Effects of supportive and conflicting interactions with partners and friends on emotions: Do the source and quality of relationships matter? - Shin, Huiyoung; Gyeong, Sunjeong (Frontiers in Psychology, 2022)
This study investigated the independent and interactive effects of supportive and conflicting interactions and overall relationship quality with partners and friends on positive and negative emotions. Data on social interactions and overall relationship quality with partners and friends, and emotions were collected from 717 South Korean adults (Mage = 47.23; 50.6% male). The results showed that supportive interactions with friends and high relationship quality with partners and friends were associated with enhanced positive emotions, whereas conflicting interactions with partners and friends and low relationship quality with partners were associated with increased negative emotions. In addition, interactive effects of social interactions and overall relationship quality suggested the evidence of reverse buffering. The beneficial effect of friend support on positive emotions was present only when friend conflict was high, and the adverse effect of partner conflict on positive emotions was magnified when individuals perceived high overall relationship quality with their partners.